2012
DOI: 10.1002/eat.22070
|View full text |Cite
|
Sign up to set email alerts
|

Increased emergency department use by adolescents and young adults with eating disorders

Abstract: Patients with eating disorders utilize the ED more frequently than those without and commonly present for complaints seemingly unrelated to their eating disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 40 publications
3
22
1
Order By: Relevance
“…When screening for such high stakes disorders, having some falsely positive screens is more acceptable than missing a significant number of true cases. This high prevalence may also be at least partially related to the known increased utilization of healthcare, including emergency departments, by individuals with eating disorders (Dooley‐Hash et al, ; Ogg et al, ; Striegel‐Moore et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When screening for such high stakes disorders, having some falsely positive screens is more acceptable than missing a significant number of true cases. This high prevalence may also be at least partially related to the known increased utilization of healthcare, including emergency departments, by individuals with eating disorders (Dooley‐Hash et al, ; Ogg et al, ; Striegel‐Moore et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…frequently than their peers (Dooley-Hash, Lipson, Walton, & Cunningham, 2013;Ogg, Millar, Pusztai, & Thom, 1997;Striegel-Moore et al, 2005). Additionally, one study found that the average number of emergency department visits correlates with greater severity of illness and higher mortality (Crow, Praus, & Thuras, 1999).…”
mentioning
confidence: 99%
“…In fact, Swanson and colleagues [ 21 ] have shown that 88% of adolescents with eating disorders have had at least one access to emergency departments, with 22% of adolescents having Binge Eating Disorder (BED). Specifically, sixteen percent of youth aged 14 to 20 years who accessed an EDpt had eating difficulties, even if not necessarily a full-blown condition [ 22 ]. Nevertheless, no specific research has been (to our best knowledge) expressly conducted to verify whether adolescent victims of road accidents are also likely to show disordered eating, one of the principal factors of vulnerability in this developmental age [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients may present with other complaints such as fatigue, abdominal pain and constipation, so that up to 50 % of cases can go undetected in the primary care setting [ 14 ]. In the emergency department the picture is similar, lack of training combined with atypical presentations has been demonstrated to result in the majority of eating disorders remaining undiagnosed for some years [ 15 ]. Another study of family physicians in the UK [ 16 ] found that females were more likely to receive a diagnosis than males, even when symptoms were identical, and overall there was a reluctance to diagnose AN, even in patients with very low weight status.…”
Section: Introductionmentioning
confidence: 99%